The tree of life: symbol of center - Azadeh pashootanizadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The interpretation of the Tree of Life is made with symbolism and mythology. This view is included in the book ID (first page of the book). The symbolic form of the tree of life is similar to the view of religions and rituals. Artists use Bible texts to illustrate the tree of life. The ancient pattern of the tree of life is associated with religious descriptions in monotheistic religions. The important thing is that the Archetype of the Tree of Life has influenced the thoughts and works of different artists from different times and styles and nations. Roger Cook, the author of this book, has been well versed in collecting a coherent set of artwork related to the ancient pattern of the tree of life, and this is a very important and sensible issue. In fact, the significance of the issue is the effect of an archetype in a common visual culture among all peoples and nations. The archetype of the tree of life, described in the religious literature, has been specially imparted in the minds and works of the arts of various artists from the classical and romantic style to the postmodern. It is interesting to conceive of a metaphysical and mystical idea by artists of nations, styles, and times. Here are some questions: 1- What is the relation between the tree in mystical thoughts and the tree in myth? 2- What steps has the tree symbol undergone in transforming from myth to art? This article is composed of library and documentary studies in a comparative study of religious literature and artwork of various nations and thus enters the analysis and description of the tree of life.